Integrasi Pendidikan Matematika dan Pendidikan Islam (Menggagas Pembelajaran Matematika di Madrasah Ibtidaiyah) - M. Imamuddin; Isnaniah Isnaniah; Zulmuqim Zulmuqim; Syafruddin Nurdin; Andryadi Andryadi (AR-RIAYAH : Jurnal Pendidikan Dasar, 2020)
Epistemologically, science and religion can be integrated, even must be integrated. Imam Suprayogo encourages science as an integration of religious values (Islam) with General Science or Science. The integration of Islamic Education and Mathematics Education in the learning proposed in this paper is Islamic education or Islamic values contained /presented/inherent in mathematics learning. Learning mathematics by incorporating Islamic values or teachings will help facilitate teachers in conveying mathematical concepts as well as Islamic education/Islamic values to students. This integrated mathematics learning is very compatible with the characteristics of Islamic schools/madrasah. Islamic values, help improve the formation of student character in accordance with the ideals of Islam and the nation.